2018
DOI: 10.3389/fsufs.2018.00017
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Co-digestion of the Organic Fraction of Municipal Solid Waste and the Liquid Fraction From the Hydrothermal Carbonization of Industrial Sewage Sludge Under Thermophilic Conditions

Abstract: The anaerobic thermophilic co-digestion of mixtures of the organic fraction of municipal solid waste (OFMSW) and the liquid fraction from the hydrothermal carbonization (LFHTC) of dewatered secondary sludge was studied. Mixtures with a low OFMSW to LFHTC ratio (50, 75, and 100% LFHTC) exhibited accumulation of volatile fatty acids (VFA) as well as low degradation of organic matter and methane production. However, the mixture containing 25% LFHTC performed quite well in terms of methane production: (179 ± 3) mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…It can be concluded that TMP did not significantly influence the separation efficiency of the process and that the 10 kDa ultrafiltration membrane allowed the removal of only up to 30% of contaminants. When comparing the three parameters used for determination of organic substances in the samples, it can be concluded that the highest efficiency of separation was observed for COD (the measure of oxidizable pollutants amount in a sample) while the lowest was for BOD It seems to be plausible to state that the liquid, with the content of such compounds, can be utilized effectively in the anaerobic digestion process, thus allowing the integration of the anaerobic digestion with HTC of its wet by-products, as already suggested by some authors [36,37,45]. Further research is needed to confirm this, assessing the influence of adding such a liquid to AD reactors and optimize the process, configured in such way (AD + HTC).…”
Section: Samplementioning
confidence: 73%
See 1 more Smart Citation
“…It can be concluded that TMP did not significantly influence the separation efficiency of the process and that the 10 kDa ultrafiltration membrane allowed the removal of only up to 30% of contaminants. When comparing the three parameters used for determination of organic substances in the samples, it can be concluded that the highest efficiency of separation was observed for COD (the measure of oxidizable pollutants amount in a sample) while the lowest was for BOD It seems to be plausible to state that the liquid, with the content of such compounds, can be utilized effectively in the anaerobic digestion process, thus allowing the integration of the anaerobic digestion with HTC of its wet by-products, as already suggested by some authors [36,37,45]. Further research is needed to confirm this, assessing the influence of adding such a liquid to AD reactors and optimize the process, configured in such way (AD + HTC).…”
Section: Samplementioning
confidence: 73%
“…These compounds were not detected for short residence times [44], which suggests that the reactions responsible for the formation of these compounds are relatively slow, and compounds can be produced in relatively long residence times, which was the case in this study. 3 139.6 Chemical oxygen demand (COD), mg O2/dm 3 31,650 Biochemical oxygen demand (BOD), mg O2/dm 3 9520 Dissolved organic carbon (DOC), mg C/dm 3 15,281 N-NH4 + , mg/dm 3 700 N-NO2 − , mg/dm 3 0.1 N-NO3 − , mg/dm 3 below the limit of detection PO4 3− , mg/dm 3 950 Na, mg/dm 3 293.6 K, mg/dm 3 688.9 Ca, mg/dm 3 28.2 Mg, mg/dm 3 449.7 Cl−, mg/dm 3 85.7 Fe, mg/dm 3 22.13 Mn, mg/dm 3 1.68 Cu, mg/dm 3 0.71 Zn, mg/dm 3 1 It seems to be plausible to state that the liquid, with the content of such compounds, can be utilized effectively in the anaerobic digestion process, thus allowing the integration of the anaerobic digestion with HTC of its wet by-products, as already suggested by some authors [36,37,45]. Further research is needed to confirm this, assessing the influence of adding such a liquid to AD reactors and optimize the process, configured in such way (AD + HTC).…”
Section: Samplementioning
confidence: 87%
“…Similarly, approximately one third of the original chemical energy of the feedstock is lost to by-products. However, this energy can be recovered by adding this liquid into anaerobic digestion reactors, as suggested by many studies of HTC of different types of biomass [43,69,[90][91][92][93][94][95].…”
Section: Resultsmentioning
confidence: 99%
“…HTC of the digestate has significant potential due to possible improvements in terms of the subsequent dewatering [52][53][54]. This process partially removes organic fraction, which could also be used as a feedstock for anaerobic digestion [55][56][57][58][59][60][61][62][63]. The potential advantages of the use of HTC for the digestate include a decrease in the overall solid mass, sanitization of the digestate and elimination of the problems related to emissions of odours from the installation, improvements of its fuel properties.…”
Section: Production Of Biocoal Using Dry and Wet Torrefactionmentioning
confidence: 99%